(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Financial services are one of the significant business outputs that pose special challenges to market them. Few of them include intangibility, inseparability, limited differentiation, and fiduciary responsibility. Contribution of financial services towards the escalation of varied segments of the economy is immense. Considering this backdrop, the present study at the outset aims at understanding different characteristics of financial services and examines the diverse challenges encountered in marketing them. This paper aims at understanding the different characteristics of financial services and examines the diverse challenges encountered in marketing them. It also brings about the difficulties people faced while availing home loans and suggests measures to overcome them. The methodology adopted here is based on secondary sources of information. The study concludes.